Dampak Pandemi Corona Virus Terhadap UMKM di Indonesia - Salma Nur Afifah (EXERO : Journal of Research in Business and Economics, 2023)
The impact of the corona virus or better known as COVID-19 has a major impact on the development of Micro, Small and Medium Enterprises (MSME). Not only in Indonesia, but almost all countries in the world, including developed countries to developing countries though. Indonesia, including a country dominated by Micro, Small and Medium Enterprises (MSME) needs to pay special attention to this sector considering the contribution of MSME   to the Indonesian economy is quite large. This research is a qualitative research type. The results of this journal research are to find out the economic and business challenges due to the COVID-19 pandemic. The purpose of this study is to analyze the impact of the Corona Virus pandemic on the existence of MSME in Indonesia and how to find solutions to help MSME survive in the current COVID-19 pandemic situation. The impact of COVID-19 has had a considerable impact on the economy in Indonesia, especially for Micro, Small and Medium Enterprises (MSME). This paper tries to analyze the impact of the COVID-19 pandemic on MSME in Indonesia and how solutions can help MSME survive in the COVID-19 pandemic situation.